ANALISIS KONTRIBUSI PENDAPATAN USAHATANI JAGUNG TERHADAP PENDAPATAN KELUARGA DI DESA KUTOSARI KECAMATAN BELITANG III KABUPATEN OKU TIMUR - Tiyas Murtiningsih; Aris Johanda (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
This study aims to determine the income and corn farming in Kutosari Village, Belitang III District, East OKU Regency and determine the level of contribution of corn farming to family income in Belitang III District, East OKU Regency. The research was carried out on the respondent's land in Kutosari Village, Belitang III OKU East District. The time for carrying out this research is October - December 2021. The method used in this research is through the survey method and the sampling method using the Purposive Sampling method (intentionally), the data collection method through structured interview techniques and literature study. The results of the study showed that the income received by respondents from corn farming in Kutosari Village was IDR 24,266,000.00/LG/MT. The average income received by respondents on corn farming in Kutosari Village is IDR 18,916,118.17/LG/MT. The details of the respondents' income can be seen in the following table. The average contribution of corn farming to total family income is 59.55%. Of the total family income of IDR 31,816,118.17, corn farming contributed 59.55% or IDR 18,916,118.17. By looking at the average contribution of corn farming income, it can be said that the contribution of corn farming income greatly determines the increase in family income.Keyword: determine, income, corn, contribution